2010
DOI: 10.1111/j.1460-9592.2010.03479.x
|View full text |Cite
|
Sign up to set email alerts
|

Probability of survival based on etiology of cardiopulmonary arrest in pediatric patients

Abstract: Probability of survival curves based on duration of CPR was statistically significantly different for CICA patients compared to RICA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 21 publications
2
16
0
3
Order By: Relevance
“…This finding is in agreement with data showing that the risk of cardio-respiratory arrest is higher in younger patients [14]. However, the association between a high PEWS and younger age could have many underlying causes, such as the emphasis on assessing signs of respiratory distress in this system: As the chest is more compliant in infants, this group is more likely to have retractions in the setting of respiratory diseases [15], and a PEWS ≥3 is therefore easier to attain.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in agreement with data showing that the risk of cardio-respiratory arrest is higher in younger patients [14]. However, the association between a high PEWS and younger age could have many underlying causes, such as the emphasis on assessing signs of respiratory distress in this system: As the chest is more compliant in infants, this group is more likely to have retractions in the setting of respiratory diseases [15], and a PEWS ≥3 is therefore easier to attain.…”
Section: Discussionsupporting
confidence: 90%
“…11,33 A multicenter study by Berens et al 34 involving 257 pediatric cardiac arrests found that patients with respiratory-induced arrest had a better survival at shorter CPR durations but that survival decreased dramatically with time, whereas survival after a cardiac-induced arrest remained unchanged with increasing duration of CPR. More recently, GWTG-R investigators reported that pediatric surgical cardiac patients are more likely to survive to hospital discharge after IHCA than those with medical cardiac or noncardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients achieve return of spontaneous circulation (ROSC), reflecting that post-resuscitation care is a major issue in outcome. [1][2][3][4][5][6][7][8][9][10][11][12][13] High mortality has mainly been attributed to the post-resuscitation syndrome, which involves hypoxia-ischemia and reperfusion, and its potential damage to the brain. [13][14][15][16][17][18][19][20][21] Neurological injury has been related to an important decrease in survival rates after IHCA in both children and adults.…”
Section: Introductionmentioning
confidence: 99%